Sprache(n) in pädagogischen Settings (De Gruyter, 2022)
This volume spans various languages and education levels, focusing on heterogeneity as an immanent characteristic of pedagogical settings. Its examines the potential of language development, the factors and facets of the developmentally appropriate promotion of German as a language of education, the conditions for successful language acquisition in the context of multilingualism, and integrative approaches toward controlled language acquisition.